IgG4-related lung disease: a case series of 6 patients and review of the literature. - Keenan, Joseph C; Miller, Elizabeth; Jessurun, Jose; Allen, Tadashi; Kim, Hyun Joo (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
IgG4 related disease has been recently proposed as a unifying term for a group of inflammatory conditions previously referred to by a plethora of other names. The common denominator for these entities is the histopathologic finding of lymphocytic infiltrates rich in IgG4 producing plasma cells, often accompanied by storiform fibrosis and obliterative phlebitis. Many medical conditions have been attributed to IgG4-related disease,but few reports of IgG4-related lung disease have been published, and it remains a rare condition about which little is known. In this report, we describe the clinical and pathologic features of six patients with IgG4-related disease of the lung. Patients were followed 1 - 5 years following their diagnosis. We describe unique features of IgG4- related lung disease, including one patient who presented with alveolar hemorrhage and a positive anti-neutrophil cytoplasmic antibody and two patients whose disease improved after treatment with mycophenylate mofetil. Two patients presented with pulmonary pseudotumor. We conclude that the clinical presentation of IgG4-related lung disease varies widely, and histopathology remains the key to diagnosis.